Effect of acceptance of illness on treatment adherence in atrial fibrillation patients - Martynow, Andrzej; Lefek, Kamila; Wierzbicka, Barbara; Chudiak, Anna; Lomper, Katarzyna; Jankowska-Polańska, Beata (Journal of Education, Health and Sport, 2017)
Introduction and aim of the study: Atrial fibrillation is the most common durable type of arrhythmia. To obtain the positive effects of treatment it necessary that the patient respects the therapeutic recommendations and cooperates with the medical staff. An important factor affecting the patients adherence to the therapeutic plan is the acceptance of the illness. The aim of the study was to assess the effect of the acceptance of illness on treatment adherence in atrial fibrillation patients. Material and methods: The study involved 105 patients with atrial fibrillation (mean age72,6; SD=6,9). The study used a medication adherence questionnaire MMAS-8 (Morisky Medication Adherence Scale) and the acceptance of illness questionaire AIS (ang. Acceptance of Illness Scale). Results: In the AIS questionnaire, the respondents received an average score of 22.67 points, which corresponds to the average level of acceptance of the illness. The results showed that 25% of the patients had low, 30% had medium, and 45% had high treatment adherence. Patients with high levels of AIS achieved high levels of treatment adherence (MMAS-8 = 8), while patients with low levels of AIS achieved low treatment adherence (MMAS-8 = 5.51). Correlation analysis showed a strong, statistically significant relationship between the level of treatment adherence and the level of illness acceptance (r = 0.7408; p = 0.01). Conclusions: The acceptance of illness significantly affects the treatment adherence in atrial fibrillation patients. The higher level of AIS determines better anticoagulation and antiarrhythmic treatment adherence in atrial fibrillation patients.